Strength properties of soils treated with calcium-based flocculants and their impact on vacuum preloading - Yan, Jinkai; Liu, Lei; Ma, Yan; Wang, Zhihui; Ren, Tianxiang (Frontiers in Earth Science, 2023)
In this study, a series of unconfined compressive strength tests were conducted to investigate the effect of calcium-based flocculants on the strength and deformation properties of slurry. The test results indicated that the presence of calcium-based flocculants (Ca(OH)2 or CaCl2) significantly enhanced the unconfined compressive strength (qu) of soil. A nonlinear relationship was observed between qu and CaCl2 content, revealing that the maximum value of qu is obtained at a CaCl2 concentration of 24.8%. qu exhibited a high increase rate at early curing time in the presence of Ca(OH)2, with a lower increase rate after a longer curing time and high Ca(OH)2 content. The deformation modulus E50 showed an increasing trend with increasing CaCl2 content at 3 and 7 d, followed by a decreasing trend with increasing CaCl2 content at 14 and 28 d. However, the failure strain εf for CaCl2 treated soil ranges from 2.4% to 4.8%, showing no relation with qu. A significant increase in E50 for Ca(OH)2-treated soil in the early curing stages (3 and 7 d) was observed because of the increase in qu. After 14 d of curing, E50 tended to decrease with increasing Ca(OH)2 content. A positive relationship between the degree of vacuum and qu in the presence of calcium-based flocculants was proposed, indicating that a higher qu of treated soil leads to a lower water content after vacuum treatment for the same preloading period, emphasizing that the vacuum treatment efficiency increases with an increase in the qu of calcium-based flocculant-treated soil.